A comprehensive review on chemical compounds, biological actions and potential health benefits of stingless bee propolis - Sharifah Nur Amalina Syed Salleh; Wan Lutfi Wan Johari; Nur Ayuni Mohd Hanapiah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Propolis mainly comprises of resins, waxes, essential oils, pollens, and impurities collected from various parts of plants such as leaf buds, mucilage, gums, and lattices. Stingless bees had been noted to produce higher amount of propolis than honey bees since they use propolis to build their nests, which makes them valuable and economical. However, very little is known about the properties of stingless bee propolis compared to honey bees’. Therefore, this review aims to highlight the chemical composition, biological actions, health benefits including some promising future research and directions of stingless bee propolis. Recent studies had shown that the chemical composition of propolis may vary according to factors such as bee species, seasonality, location and floral preferences. These compounds play a major role in the biological and medical efficacy exhibited by the propolis. Stingless bee propolis is also known to display potent therapeutic and biological properties such as antioxidant, antimicrobial, antifungal and many more that could be used to treat diseases, infections and disorders effectively. The insights provided in this review may helpfully enhance the utility of stingless bee propolis for their therapeutic and health benefits in the food, pharmacological and medicinal sectors, some which are yet to be fully discovered.